(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Deformities of the lower limbs are very common in children, mostly physiological and need no treatment at all. Ninety percent of clinic visits for foot problems are due to flatfoot, Aim and objectives was to test validity and efficacy of subtalar arthroereisis technique in treatment of pediatric and adolescents’ flexible flatfeet that was operated at orthopedic department Beni Suef University Hospital, Subjects and methods A prospective study was carried out on 19 patients (30 feet) with painful idiopathic flexible flatfeet in the period between June 2019 and June 2021. All cases were selected from the foot and ankle outpatient clinic of Beni Suef University hospital, Result One patient (3.3%) had Persistent sinus tarsi pain with backing out of the screw, 6 months following surgery, which improved following screw removal and the foot maintained correction, one patient (3.3%) had Screw backed out 2 months following surgery and revision was done with a larger screw , Conclusion The subtalar arthroereisis technique is able to improve the clinical and radiological parameters with a minimal invasive surgery and fewer complications.